using suitable identify, evaluate the following: 1) 101×102 (2) 97×103
Answers
Answered by
16
Hello friends!!!
Here is your answer :
( 1 )
![101 \times 102 101 \times 102](https://tex.z-dn.net/?f=101+%5Ctimes+102)
![(100 + 1)(100 + 2) (100 + 1)(100 + 2)](https://tex.z-dn.net/?f=%28100+%2B+1%29%28100+%2B+2%29)
Using identity :
( x + a) ( x + b) = x² + ( a + b)x + ab
x = 100
a = 1
b = 2
![= > {(100)}^{2} + (1 + 2)100 + (1)(2) = > {(100)}^{2} + (1 + 2)100 + (1)(2)](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%7B%28100%29%7D%5E%7B2%7D++%2B+%281+%2B+2%29100+%2B+%281%29%282%29)
![= > 10000 + 3(100) + 2 = > 10000 + 3(100) + 2](https://tex.z-dn.net/?f=+%3D++%26gt%3B+10000+%2B+3%28100%29+%2B+2)
![= > 10000 + 300 + 2 = > 10000 + 300 + 2](https://tex.z-dn.net/?f=+%3D++%26gt%3B+10000+%2B+300+%2B+2)
![= > 10302 = > 10302](https://tex.z-dn.net/?f=+%3D++%26gt%3B+10302)
_________________
( 2)
![97 \times 103 97 \times 103](https://tex.z-dn.net/?f=97+%5Ctimes+103)
![(100 - 3)(100 + 3) (100 - 3)(100 + 3)](https://tex.z-dn.net/?f=%28100+-+3%29%28100+%2B+3%29)
Using identity :
( a - b) ( a + b) = a² - b²
![= > {(100)}^{2} - {(3)}^{2} = > {(100)}^{2} - {(3)}^{2}](https://tex.z-dn.net/?f=+%3D+++%26gt%3B++%7B%28100%29%7D%5E%7B2%7D++-+++%7B%283%29%7D%5E%7B2%7D+)
![= > 10000 - 9 = > 10000 - 9](https://tex.z-dn.net/?f=+%3D++%26gt%3B+10000+-+9)
![= > 9991 = > 9991](https://tex.z-dn.net/?f=+%3D++%26gt%3B+9991)
__________
Hope it helps you..
☺️☺️☺️☺️
# Be Brainly
Here is your answer :
( 1 )
Using identity :
( x + a) ( x + b) = x² + ( a + b)x + ab
x = 100
a = 1
b = 2
_________________
( 2)
Using identity :
( a - b) ( a + b) = a² - b²
__________
Hope it helps you..
☺️☺️☺️☺️
# Be Brainly
Cutiepie93:
please Mark it as brainliest
Answered by
1
I hope you have help this answer
Attachments:
![](https://hi-static.z-dn.net/files/d2d/5ed20411f9babd8bd0358b652060f972.jpg)
Similar questions